3(x+1)=9(x-2)

Simple and best practice solution for 3(x+1)=9(x-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x+1)=9(x-2) equation:


Simplifying
3(x + 1) = 9(x + -2)

Reorder the terms:
3(1 + x) = 9(x + -2)
(1 * 3 + x * 3) = 9(x + -2)
(3 + 3x) = 9(x + -2)

Reorder the terms:
3 + 3x = 9(-2 + x)
3 + 3x = (-2 * 9 + x * 9)
3 + 3x = (-18 + 9x)

Solving
3 + 3x = -18 + 9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9x' to each side of the equation.
3 + 3x + -9x = -18 + 9x + -9x

Combine like terms: 3x + -9x = -6x
3 + -6x = -18 + 9x + -9x

Combine like terms: 9x + -9x = 0
3 + -6x = -18 + 0
3 + -6x = -18

Add '-3' to each side of the equation.
3 + -3 + -6x = -18 + -3

Combine like terms: 3 + -3 = 0
0 + -6x = -18 + -3
-6x = -18 + -3

Combine like terms: -18 + -3 = -21
-6x = -21

Divide each side by '-6'.
x = 3.5

Simplifying
x = 3.5

See similar equations:

| x^4-14x^3+40x^2=-1 | | (4/9)x=8/27 | | 6n-4-3n=2n+9+4n-20 | | (5x-6)*(5x-6)-81=0 | | 1/64=(√2)^x | | (Y-3)*2= | | 5t=3t+10 | | 25=6(x)+35 | | 5j/9=4/4 | | (x^3)-(3*x)-3=0 | | 4x+3y=2y-5x+12 | | 11x/10-4x/5=12 | | x^4-14x^3+40x^2-1=0 | | 0.75+7x^2=9 | | 3(x+2)-4=5x-2(-2+x) | | 9x(x+5)-5(x+5)=0 | | 4x^3+.76x^2+.0361x-.0000000000561=0 | | 3(2x-2y)=4(x+y) | | 7=3t-3t+4t+3t | | 1/3y-6=12 | | 2x-120=230 | | 9k^2+8+0=0 | | 20=14c-4c+2c-5c-2c | | -4(5t-5)+5t=6t-2 | | 2(2x-3y)=36 | | -9=2c-c+2c | | 5=8q-5q-2q | | 8x-9x^2=0 | | -4(5t-5)=6t-2 | | 10h-30h-7h+49=4h | | 16=9r-4r-2r-2r | | 6y+9=3y-15 |

Equations solver categories